ClassPoint Training for Supporting Interactive and Inclusive Learning Among Teachers at SMA PGRI Pekanbaru - M Fadhly Farhy Abbas; Budianto Hamuddin; Tatum Derin; Meutya Rizki Ramadhani; Fatma Setya Ningrum (Bhinneka Publishing, 2026)
This community service activity aimed to improve teachers’ readiness in implementing interactive and inclusive learning through ClassPoint training at SMA PGRI Pekanbaru. The activity was conducted on April 29, 2026, involving 15 high school teachers from various subject backgrounds. The program was carried out through several stages, including preparation, introduction to interactive learning concepts, hands-on ClassPoint training, guided practice, and evaluation of participants’ responses toward the activity. During the training, teachers were introduced to various interactive features such as quizzes, word clouds, and real-time response systems integrated with PowerPoint. The activity results showed that teachers demonstrated positive responses toward the training and increased confidence in using interactive technology in classroom instruction. Teachers also reported that ClassPoint could help create more engaging, student-centered, and inclusive learning environments. Overall, the training activity contributed positively to teachers’ technological readiness and pedagogical awareness in implementing interactive learning practices. Continuous training and institutional support are recommended to ensure the sustainable integration of interactive technology in classroom teaching.